EVALUASI SISTEM DAN PROSEDUR PENGELUARAN KAS BELANJA LANGSUNG PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH PROVINSI SULAWESI UTARA - Kasakeyan, Bella Angelina; Karamoy, Herman; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
A successful government is a government that always provides public services by applying the character of good goverance. One of the important things to achieve the character of good governance is the evaluation of cash expenditures. Cash expenditures are used for various types of payments, one of which is direct expenditure and is very important to support the implementation of government programs that have been previously planned. Cash expenditures procedures consist of: 1) Issuance of a letter of provision of funds, 2) Submission of a request for payment, 3) Issuance of a payment order, 4) Issuance of a warrant for disbursing funds, and 5) Issuance of a letter accountability. The analytical method used is descriptive analysis method. The result of the study showed that the implementation of the system and procedure for the direct expenditure of cash expenditures at the Regional Industry and Trade Office of North Sulawesi Province was in accordance with the applicable laws and regulations. So it can be concluded that the application of the system and procedure for the direct expenditure of cash expenditure at the Regional Industry and Trade Office of North Sulawesi Province has been carried out properly and in accordance with Minister of Home Affairs Regulation number 21 of 2011.